Respostas

2014-08-11T13:45:31-03:00
X²+6x-27=0
a=1  b=6  c=-27

Δ=6² - 4 . 1 . (-27)
Δ=36+108
Δ=144

x'=-6+√144 -----> -6+12 ------> 6 -----> 3
       2.1                  2                2
x"=-6-√144 -----> -6-12 -------> -18 ------> -9
          2.1                  2               2

x'= 3 e x"= -9

Espero ter ajudado.


1 5 1
2014-08-11T14:05:06-03:00
x²+6x-27=0    coeficientes: a: 1  b: 6  c: -27

Δ= (6)² -4 (1) (-27)
Δ= 36 + 108
Δ= 144

X= -6 +- 12 = X
₁ = -6 + 12 = 6 = 3     X₂ = -6 -12 = - 18 = -9
          2                     2         2                    2             2

Portanto: X
₁ = 3  e X₂ = -9